2022
DOI: 10.1186/s42483-022-00135-z
|View full text |Cite
|
Sign up to set email alerts
|

Multiomic approaches reveal novel lineage-specific effectors in the potato and tomato early blight pathogen Alternaria solani

Abstract: The effectome of the necrotrophic fungal pathogen, Alternaria solani, was determined using multiomics. In total, 238 effector candidates were predicted from the A. solani genome, and apoplastic effectors constitute most of the total candidate effector proteins (AsCEPs). Comparative genomics revealed two main groups of AsCEPs: lineage-specific and conserved effectors. RNA-Seq analysis revealed that the most highly expressed genes encoding AsCEPs were enriched with lineage-specific forms. Two lineage-specific ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 70 publications
0
14
0
Order By: Relevance
“…A transcriptome analysis of the genes in potato and A. solani that exhibited interactions in the early infection stage showed that cell wall-degrading enzymes and metabolic processes may be important for early A. solani infection of potato [ 14 ]. In our previous study, we reported that the effector proteins AsCEP112, AsCEP19 and AsCEP20, and play important roles in late-stage A. solani infection of potato leaves [ 15 , 16 ]. In the current study, we inoculated potato leaves with A. solani and found that near the inoculation site, there were obvious whorl symptoms and tissue collapse within 72 h, and the disease spread rapidly between 96 and 120 h. Therefore, we focused on protein interaction in the late stage of infection, which was further investigated by genome-wide transcriptomic analyses.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A transcriptome analysis of the genes in potato and A. solani that exhibited interactions in the early infection stage showed that cell wall-degrading enzymes and metabolic processes may be important for early A. solani infection of potato [ 14 ]. In our previous study, we reported that the effector proteins AsCEP112, AsCEP19 and AsCEP20, and play important roles in late-stage A. solani infection of potato leaves [ 15 , 16 ]. In the current study, we inoculated potato leaves with A. solani and found that near the inoculation site, there were obvious whorl symptoms and tissue collapse within 72 h, and the disease spread rapidly between 96 and 120 h. Therefore, we focused on protein interaction in the late stage of infection, which was further investigated by genome-wide transcriptomic analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, few reports have focused on the pathogenic effectors of A. solani in potato. In our previous study, the important effector proteins AsCEP112, AsCEP19 and AsCEP20 were identified [ 15 , 16 ]. AsCEP112 is an important effector protein that targets host cell membranes and regulates host senescence-related genes to control host leaf cell senescence and chlorosis, and contributes to pathogen virulence [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The amino acid sequences of βCA, SBP, and FBA in the examined plant species were separately subjected to multiple alignment using fast Fourier transform (MAFFT) ( Jasim et al., 2020 ) to generate multiple sequence alignments with default parameters for revealing the evolutionary history. ProtTest was used to estimate the best model in this analysis for finding the amino acid substitution model that best fitted our data ( Wang et al., 2022 ). The JTT+ Gamma model was the best-fit model for the βCA and SBP protein datasets, whereas the JTT model was the best amino acid substitution model for the FBA protein dataset.…”
Section: Methodsmentioning
confidence: 99%
“…solani were cultured on potato dextrose agar (PDA) for strain activation and tomato juice agar medium (T4) to induce sporulation. The activated HWC-168 strain was transferred to a T4 medium plate, cultured in the dark at 25°C for 7 to 10 days, then scraped off the mycelia, UV irradiated for 10 minutes (Ultraviolet lamp power is 8 W), nally the plate was cultured in the dark at 25°C/20°C alternately for 3 days [15].…”
Section: Plant Growth and Infection Conditionsmentioning
confidence: 99%